2012
DOI: 10.1007/s12104-012-9444-4
|View full text |Cite
|
Sign up to set email alerts
|

1H, 13C and 15N chemical shift assignments of Na-FAR-1, a helix-rich fatty acid and retinol binding protein of the parasitic nematode Necator americanus

Abstract: The fatty acid and retinol-binding (FAR) proteins are a family of unusual helix-rich lipid binding proteins found exclusively in nematodes, and are secreted by a range of parasites of humans, animals and plants. Na-FAR-1 is from the parasitic nematode Necator americanus, an intestinal blood-feeding parasite of humans. Sequence-specific 1H, 13C and 15N resonance assignments have been obtained for the recombinant 170 amino acid protein, using three-dimensional triple-resonance heteronuclear magnetic resonance ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…Our next step was to identify a method to efficiently remove bacterial ligands from the proteins. Despite published precedent [ 35 ], we found that chromatography with Lipidex 1000 is ineffective at removing lipid from helminth LBPs [ 39 , 57 , 58 ]. We therefore exploited a method for removal of co-purifying ligands from other recombinant LBPs produced in E .…”
Section: Resultscontrasting
confidence: 59%
“…Our next step was to identify a method to efficiently remove bacterial ligands from the proteins. Despite published precedent [ 35 ], we found that chromatography with Lipidex 1000 is ineffective at removing lipid from helminth LBPs [ 39 , 57 , 58 ]. We therefore exploited a method for removal of co-purifying ligands from other recombinant LBPs produced in E .…”
Section: Resultscontrasting
confidence: 59%
“…Recombinant Na-FAR-1 (rNa-FAR-1) was expressed in BL21 (λDE3) Escherichia coli cells as described [ 27 ]. For native crystallographic studies, Na-FAR-1 was purified to homogeneity, as previously described [ 28 ], from cells grown in LB media.…”
Section: Methodsmentioning
confidence: 99%
“…For NMR studies, samples of unlabelled, 15 N-labelled and 13 C 15 N-labelled protein were purified by nickel-affinity, size exclusion and reverse-phase chromatographies, as described [ 27 ], from cells grown in M9 minimal medium containing 15 NH 4 Cl, [ 13 C 6 ]-glucose or their unlabelled equivalents.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations